Growth and project finance in the least developed countries - Lisbeth F. la Cour; Jennifer Müller (International Journal of Economic Sciences and Applied Research, 2014)
This article examines the effects of project finance on economic growth in the least developed countries (LDC). Inspired by the neoclassical growth model we set up an econometric model to estimate the effects of project finance for a sample consisting of 38 of the least developed countries using data from the period 1994-2007. The results of our study suggest, that project finance has a significant positive effect on economic growth and therefore constitute an important source of financing in the selected set of countries. Additionally, the project sheds light on other factors of importance for economic growth in LDCs. We find that a higher regulatory quality, lower government consumption and a higher level of education helps increase growth. The significance of these variables are, however, not as consistently robust as the results for project finance.
Keywords: F43; G15; O16; 330; Project Finance; Economic Growth; Least Developed Countries; Foreign Direct Investment